Combining ability studies in castor (Ricinus communis L.) under irrigated and un-irrigated environments: COMBINING ABILITY STUDIES IN CASTOR - N SASIDHARAN; G C JADEJA; M M BHATT (Journal of Oilseeds Research, 2013)
Forty eight hybrids developed through L x T design (four females and 12 males) were evaluated under irrigated and unirrigated environments for computing estimates of general and specific combining ability effects for 14 quantitative and qualitative charactersincluding castor(Ricinus communisL.)seed yield.Combining ability analysis revealed that gca variances were significant, only for few characters, under both environments; whereas sca variances were significant for all the characters in both the environments, reiterating the preponderance of non-additive gene action in the inheritance of these characters. The female parents, SKP-84 and SKP-49 and male parents viz.,JI-224,JI-244,JI-260, SKI-160, SKI-202 and SKI-232 were superior and consistent general combiners for seed yield and other yield contributing characters. For oil content, the parents SKP-49, SKI-202, SKI 232 and JI-260 were superior general combiners under irrigated environment, whereas under the un-irrigated situation, SKP-84, JP-82, JI 263 and JI-258 were the good general combiners. The hybrids which recorded high sca effects forseed yield wereGeetha x JI-224 and SKP-49 x JI-227 under irrigated and un-irrigated environments, respectively. Looking to the importance of both additive and non-additive gene action in the inheritance of various characters, a breeding strategy involving biparental matings coupled with reciprocal recurrent selection may be employed for simultaneous improvement of the characters.